2019
DOI: 10.1007/s12663-019-01269-y
|View full text |Cite
|
Sign up to set email alerts
|

Current Orthognathic Practice in India: Do We Need to Change?

Abstract: The last decade or so has seen paradigm shifts in the various aspects of orthognathic surgery. A lot of these changes are to do with digitalization of the orthodonticsurgical workflow, optimization of surgery-first protocols, virtual surgical planning-based 3D printing solutions and changing patient-health-care dynamics. The aim of this article is to provide evidence-based recommendations that are both practical and economically viable for the current orthognathic practice in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…A study from our institution showed that with implementation of these guidelines, our surgical workload equaled 60% of that during a similar period during last year. 15 Based on the findings of this survey, we incorporated steps to reduce the delay in the work execution and provided more secretarial assistance to the medical staff to reduce their increased workload created by implementing the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…A study from our institution showed that with implementation of these guidelines, our surgical workload equaled 60% of that during a similar period during last year. 15 Based on the findings of this survey, we incorporated steps to reduce the delay in the work execution and provided more secretarial assistance to the medical staff to reduce their increased workload created by implementing the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in concordance with the data from most other centres 18 , 19 , which clearly show that the postoperative outcomes remain unchanged with no added risk or a minimal risk of SARS-CoV-2 infections in healthcare personnel. Iyer et al reported that there was a reduction in number of cases (overall operative caseload) to about 60% of the pre-COVID-19 times in order to maintain adequate safety and implement protective measures for COVID-19 transmission 20 .…”
Section: Discussionmentioning
confidence: 99%